Analysis of Students' Mathematical Concept Understanding Ability in Multiplication Calculation Operation Material (Current Research in Education: Conference Series Journal, 2024)
This study aims to investigate fourth-grade students’ understanding of mathematical concepts in solving multiplication problems. A qualitative descriptive method was used, involving 28 elementary school students in Bandung, Indonesia. Data were collected through questionnaires, interviews, and documentation, and analyzed using data collection, reduction, display, and conclusion techniques. The test instrument consisted of three descriptive questions with indicators of restating ideas, representing concepts mathematically, and applying algorithmic concepts in problem-solving. An unstructured interview was also conducted to identify students’ learning challenges. The results showed that 64% of students could restate a concept, 68% could represent concepts mathematically, and only 18% could apply algorithmic concepts to solve problems. Overall, students’ comprehension of mathematical concepts in multiplication procedures was relatively low, with an average achievement of 50%. Factors contributing to this low understanding include lack of attention, inconsistent study habits, and unengaging teaching methods. These findings highlight the need for more effective instructional strategies that emphasize conceptual understanding, student engagement, and consistent learning habits to improve students’ ability to apply mathematical principles in problem-solving